(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Israel has established itself as a global leader in smart agriculture, leveraging technological innovation to enhance agricultural efficiency and sustainability. This study examines Israel’s contributions to smart agriculture and its mechanisms for technology transfer, with a particular focus on its cooperation with China. The topicality of this research lies in the growing global demand for sustainable agricultural solutions, driven by climate change, resource scarcity, and food security challenges. Israel’s expertise in precision farming, drip irrigation, agri-biotechnology, and water resource management has made it a key partner in international agricultural development, with China serving as a prominent recipient of its technological innovations. The purpose of this study is to analyse the mechanisms and effectiveness of Israel’s agro-technology transfer, assessing its impact on China’s agricultural sector and its replicability in other national contexts. The research explores the role of public-private partnerships, government policies, innovation hubs, and financial protocols in facilitating international technology transfer. This study employs a mixed-methods approach, combining case study analysis, policy reviews, expert interviews, and on-site observations. Primary data was gathered through fieldwork at China-Israel Technology Transfer Centres, interviews with local agricultural stakeholders, and reviews of bilateral agreements. Secondary data includes government reports, legislative documents, and academic literature on technology transfer and smart agriculture. The findings indicate that Israel’s structured, government-backed approach to technology transfer has led to successful adaptation and implementation of its agro-technologies in China. The China-Israel cooperation serves as a model for other nations, demonstrating the importance of strategic frameworks, knowledge-sharing platforms, and capacity-building programs in agricultural modernisation. However, challenges remain, including bureaucratic barriers, differences in regulatory frameworks, and the need for localised adaptations. This study concludes that Israel’s technology transfer model represents a scalable and effective strategy for addressing global agricultural challenges. Strengthening international cooperation, fostering innovation-driven policies, and enhancing financial support for technology adoption are key recommendations for advancing global sustainable agriculture.